Novos modelos de sobrevivência com fração de cura baseados no processo da carcinogênese - Borges, Patrick (2012)
In this dissertation we propose new models for survival with cure fraction to describe the biological mechanism of the event of interest (cancer) in studies of carcinogenesis in the presence of competing causes latent independent or correlated. The formulation of new models is based on stochastic modeling of the occurrence of tumors through three stages: initiation of a tumor not detectable, promotion and progression of the tumor to a detectable cancer. These models allow a simple pattern of the dynamics of tumor growth, and incorporate into the analysis features of the stage of tumor progression that is not possible in most survival models with cure fraction commonly used. For the proposed models, the inferential process was discussed in terms of classical and Bayesian point of view. Simulations studies were conducted in order to analyze the asymptotical properties of the classical estimation procedure. Real data applications demonstrate of use of the models.